Therapeutic effect of trephine resection combined with fractional ablative CO2 laser in the treatment of pitted acne scars - Yanhong ZHANG; Yucheng HUANG; Hui XU; Xiaoyu CHEN; Yimeng LIU; Xiaopan FAN; Linlin SUN (Pifu-xingbing zhenliaoxue zazhi, 2023)
Objective To evaluate the efficacy and safety of trephine resection combined with fractional ablative CO2 laser for pitted acne scars. Methods Sixty eight patients with facial pitted acne scars were enrolled from the Medical Cosmetology Center of Zhengzhou People's Hospital from February 2019 to February 2022. The patients were randomly divided into the observation (30 patients) and the control groups (38 patients). The observation group was treated with trephine resection combined with CO2 laser, and the control group was treated with fractional ablative CO2 laser alone. The efficacy and the ECCA scale (Echelle d 'Evaluation Clinique des Cicatrices d 'acne) were compared between the two groups after 6-month treatment. Results Before the treatment, ECCA scores were comparable between the observation and the control groups [50.00 (43.75, 60.00) vs. 47.50 (37.50, 60.00), P=0.535]. After 6-month treatment, the ECCA scores in both groups were significantly lower than the baseline (both P<0.01), and the ECCA scores were significantly lower in the observation group [20.00 (15.00, 30.00)] than in the controls [25.00 (20.00, 30.00)] (P=0.032). The effective rate in the observation group was significantly higher than that in the controls (93.33% vs. 71.05%, P=0.020). But adverse reactions did not differ significantly between the two groups(P=1.000). Conclusions Trephine resection combined with fractional ablative CO2 laser is more effective than fractional ablative CO2 laser alone for facial pitted acne scars and is safe.